Tribal rights in India - Devi,K.Uma (ed.) (New Delhi, 2006)
The articles contributed by authors to this issue provide a panoramic view of the various provisions in national legislations as well as of the Multilateral Conventions and Treaties, tracing them from their evolutionary stage. The articles also highlight the limitations and atrocities caused to economic, social and cultural rights of tribal. people, including tribal children, of India. The stark and gross violation of not only human rights but also their i rights to be human is demonstrated by the empirical study of the tribal people in various districts in India. The tribal people have been deprived, displaced and dispossessed of their cultural and traditional rights too under the garb of development of the districts inhabited by them.
Keywords: Scheduled tribes-India-civil rights